PENGUJIAN PERBANDINGAN KETAHANAN BERBAGAI BUSI SEPEDA MOTOR DENGAN MENGGUNAKAN ALAT BUSI TESTER - Hasan, Indra; Denur (Fakultas Teknik UMRI, 2022)
The development of automotive technology is very fast, we can find this in today's vehicles that use a lot of very sophisticated technology, namely in terms of engines, electricity, and its newest features, especially on two-wheeled vehicles. Therefore, the user community is required to be more selective in choosing a vehicle both in terms of quality and quantity. Including in the selection of spare parts on vehicle engines must use good quality, this is useful as a motorbike power booster, especially in the ignition system, namely spark plugs as a vital tool that sprinkles sparks in the combustion chamber. Recently, many spark plugs have been found that are not good enough so that the power generated by the vehicle is reduced. The purpose of this test is as a Comparative Test of the Endurance of Various Motorcycle Spark Plugs by using a spark plug tester so that it can be seen that the spark plug is suitable or not used in the vehicle which aims to get maximum performance.